Increased temporal discounting in bulimia nervosa. Issue 12 (15th June 2016) - Kekic, Maria; Bartholdy, Savani; Cheng, Jiumu; McClelland, Jessica; Boysen, Elena; Musiat, Peter; O'Daly, Owen G.; Campbell, Iain C.; Schmidt, Ulrike
ABSTRACT: Objective: There is evidence that people with eating disorders display altered intertemporal choice behavior (the degree of preference for immediate rewards over delayed rewards). Compared to healthy controls (HC), individuals with anorexia nervosa and binge‐eating disorder show decreased and increased rates of temporal discounting (TD; the devaluation of delayed rewards), respectively. This is the first study to investigate TD in people with bulimia nervosa (BN). Method: Thirty‐nine individuals with BN (2 men) and 53 HC (9 men) completed a hypothetical monetary TD task. Over 80 binary choices, participants chose whether they would prefer to receive a smaller amount of money available immediately or a larger amount available in 3 months. Self‐reported ability to delay gratification (the behavioral opposite of TD) was also measured. Results: Individuals with BN showed greater TD (i.e., a preference for smaller‐sooner rewards) and a decreased self‐reported capacity to delay gratification relative to HC. Experimental groups did not differ in age, gender ratio, or BMI. Discussion: Increased rates of TD may contribute to some of the core symptoms of BN that appear to involve making choices between immediate and delayed rewards (i.e., binge‐eating and compensatory behaviors). Altered intertemporal choice behavior could therefore be a relevant target for intervention in this patient group. © 2016 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:1077–1081)